Green brand innovation dan green brand loyalty: Peran moderasi green knowledge - Tyas Carin Anjellika; Muhammad Ali Fikri (Jurnal STEI Ekonomi, 2025)
The background of this study is based on the increasing awareness of environmental issues and the importance of green brand innovation in building customer loyalty to a brand. This study aims to analyze the impact of green brand innovation on green brand loyalty and to examine the moderating role of green knowledge among users of Livin' by Mandiri m-banking services. A quantitative approach was applied through a survey method involving 167 respondents using purposive sampling techniques. Data analysis was conducted using moderation regression techniques to evaluate the interaction between the variables studied. The results of the study revealed that green brand innovation has a positive effect on green brand loyalty, green knowledge has a positive effect on green brand loyalty, and green knowledge does not act as a moderator in the effect of green brand innovation on green brand loyalty. These findings indicate that green knowledge does not affect the strength of the relationship between green brand innovation and green brand loyalty. These findings provide strategic implications for Bank Mandiri to optimize sustainable innovation and consumer education programs in building long-term loyalty.